1995
DOI: 10.1111/j.1526-4610.1995.hed3506315.x
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Study of Headache Associated With Ischemic Stroke

Abstract: Thirty-four percent of 182 ischemic stroke patients registered during 1 year in a prospective hospital stroke data base complained of headache within a 72-hour interval of stroke onset. Headache was more common in patients under 70 years of age, in nonsmokers, in those with a past history of migraine, and in subjects presenting transient loss of consciousness, nausea/vomiting, or visual field defects. Headache was more frequent in vertebrobasilar (57%) than in carotid (20%) territory strokes, more so in poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
98
2
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 6 publications
11
98
2
1
Order By: Relevance
“…Infarctions in the cerebellum, medulla, or posterior cerebral artery cortex are more likely to be associated with onset headache compared with other regions. The cerebellum and posterior cerebral artery cortex have been implicated in prior studies, 15,16 but the medulla is being reported for the first time, in the present study. Although the cerebellum is insensitive to pain, the vertebral artery and posterior inferior cerebellar arteries that supply both the medulla and cerebellum are sensitive to pain.…”
Section: July 2013supporting
confidence: 55%
See 1 more Smart Citation
“…Infarctions in the cerebellum, medulla, or posterior cerebral artery cortex are more likely to be associated with onset headache compared with other regions. The cerebellum and posterior cerebral artery cortex have been implicated in prior studies, 15,16 but the medulla is being reported for the first time, in the present study. Although the cerebellum is insensitive to pain, the vertebral artery and posterior inferior cerebellar arteries that supply both the medulla and cerebellum are sensitive to pain.…”
Section: July 2013supporting
confidence: 55%
“…[6][7][8][9][10][11][12] Most previous studies do not specify these differences and as such, the frequencies of stroke-related headache vary from 8% to 34%. [1][2][3][4][8][9][10][11][12][13][14][15][16][17][18] In fact, stroke-related headache at different time points may result from different mechanisms and may have varying clinical effects. A large sample of patients with stroke-related headache in a well-defined time frame and a systematic follow-up of clinical features and outcomes are required to delineate the clinical impact of stroke-related headaches.…”
mentioning
confidence: 99%
“…4,[8][9][10][11][12][13][14][15][16] In addition, we found that patients who developed headaches after tPA administration were younger, which is consistent with a previous observation. 17 One previous study reported a higher incidence of headache in cardioembolic infarcts than in TIAs, lacunar infarcts, or thrombotic infarcts.…”
Section: Discussionsupporting
confidence: 81%
“…7 An inverse association between headache and age has been found in other cerebrovascular disorders. 8,9 Patients without headache also more often had seizures. Some of these patients might not recall a headache that occurred before the seizure.…”
Section: Discussionmentioning
confidence: 99%